The role of transdisciplinary approach and community participation in village scale groundwater management: insights from Gujarat and Rajasthan, India - Maheshwari, B.; Varua, M.; Ward, J.; Packham, R.; Chinnasamy, Pennan; Dashora, Y.; Dave, S.; Soni, P.; Dillon, P.J.; Purohit, R.; Hakimuddin; Shah, Tushaar; et al. (MDPI, 2014)
Sustainable use of groundwater is becoming critical in India and requires effective participation from local communities along with technical, social, economic, policy and political inputs. Access to groundwater for farming communities is also an emotional and complex issue as their livelihood and survival depends on it. In this article, we report on transdisciplinary approaches to understanding the issues, challenges and options for improving sustainability of groundwater use in States of Gujarat and Rajasthan, India. In this project, called Managed Aquifer Recharge through Village level Intervention (MARVI), the research is focused on developing a suitable participatory approach and methodology with associated tools that will assist in improving supply and demand management of groundwater. The study was conducted in the Meghraj watershed in Aravalli district, Gujarat, and the Dharta watershed in Udaipur district, Rajasthan, India. The study involved the collection of hydrologic, agronomic and socio-economic data and engagement of local village and school communities through their role in groundwater monitoring, field trials, photovoice activities and education campaigns. The study revealed that availability of relevant and reliable data related to the various aspects of groundwater and developing trust and support between local communities, NGOs and government agencies are the key to moving towards a dialogue to decide on what to do to achieve sustainable use of groundwater. The analysis of long-term water table data indicated considerable fluctuation in groundwater levels from year to year or a net lowering of the water table, but the levels tend to recover during wet years. This provides hope that by improving management of recharge structures and groundwater pumping, we can assist in stabilizing the local water table. Our interventions through Bhujal Jankaars (BJs), (a Hindi word meaning “groundwater informed” volunteers), schools, photovoice workshops and newsletters have resulted in dialogue within the communities about the seriousness of the groundwater issue and ways to explore options for situation improvement. The BJs are now trained to understand how local recharge and discharge patterns are influenced by local rainfall patterns and pumping patterns and they are now becoming local champions of groundwater and an important link between farmers and project team. This study has further strengthened the belief that traditional research approaches to improve the groundwater situation are unlikely to be suitable for complex groundwater issues in the study areas. The experience from the study indicates that a transdisciplinary approach is likely to be more effective in enabling farmers, other village community members and NGOs to work together with researchers and government agencies to understand the groundwater situation and design interventions that are holistic and have wider ownership. Also, such an approach is expected to deliver longer-term sustainability of groundwater at a regional level.